algebra
 👍 0
 👎 0
 👁 126

 👍 0
 👎 0
Respond to this Question
Similar Questions

math
10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use

PreCalc
Approximate the solutions to the following equation on the interval [0,2π). Round your answer to four decimal places. sinθ=0.65 Apparently, there suppose to be two answers to this question with a comma separating both

math
Consider the sequence of steps to solve the equation: 5(x  3) = 7x 2 Step 1 ⇒ 10(x  3) = 7x Step 2 ⇒ 10x  30 = 7x Step 3 ⇒ 3x  30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

MATHALGEBRA
What's the slopeintercept equation of line which is parallel to y = 2/5x3 and passes through point (0,5) A. y = 5/2x  3 B. y = 5/2x + 5 C. y = 2/5x + 3 D. y = 2/5x + 5 Its D, but how do u figure that out? please explain step

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

Geometry
Geometric Proofs.... Write a justification for each step Given: AB = EF, B is the midpoint of Line AC and E is the midpoint of Line DF. 1. B is the midpoint of Line AC and E is the midpoint of Line DF. 2. Line AB is congruent to

math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

math
Omar wanted to know if x−5 is a factor of the polynomial p(x)=x3−6x2−x+30. He applied the Factor Theorem and concluded that x−5 is a factor of p(x), as shown in the following work. Step 1: p(5)=53−6(52)−5+30 Step 2:

Math
Davide wants to find the zeros of the polynomial p(x)=x3−2x2−9x+18. His work is shown below. Step 1: p(x)=(x+3)(x−3)(x−2) Step 2: x+3=0 x−3=0 x−2=0 Step 3: x=2, x=3, x=−3 Explain why Davide’s work shows that 2, 3,

Help PLZ!!
consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: 4 3 7 + 7 + (3 4 7 ) Step 1: = 4 3 7 + (3 4 7 ) + 7 Step 2: = 4 + ( 3 7 ) + (3) + ( 4 7 ) + 7 Step 3: = 4 + ( 3 7 ) + (

Calculus
The function g is defined for x>0 with g(1)=2, g'(x)=sin(x+1/x), and g"(x)=(11/x^2)cos(x+1/x). A. Find all values of x in the interval 0.12
You can view more similar questions or ask a new question.